Infrastructural Deterioration and Outcomes of the 2019 Gubernatorial Elections in Bauchi State, Nigeria - Gar, Ruqayya, Aminu; Umar, Mohammed, Nuru (My University, 2022)
Infrastructure comprising road and rail network, health care, and educational facilities have powerful effects on the overall electoral process of people in various political entities. They also play a determining role in setting the bases of the voting choice and change in the orientations of the people towards their political system. Reports on infrastructure in Bauchi state exist but are incomplete to academic principles. This study examines infrastructure deterioration and the outcome of the 2019 gubernatorial elections in Bauchi state Nigeria through a qualitative method of data collection and analysis. Findings of the e study concludes that, part of the underlying principle for the success of an opposition political party, the Peoples Democratic Party (PDP) in the 2019 gubernatorial elections includes. The electorates’ assessments of the All Progressives Congress (APC) administration’s discouraging records in the provision and maintenance of Infrastructure comprising: road and rail network, health care system, and educational facilities. Better election campaign strategy and reliable contestant offered by opposition parties; and enhanced training by the electoral body, the Independent National Electoral Commission (INEC). This confirms the significance of Infrastructure (road and rail network, health care, and educational facilities) as crucial factors influencing electoral outcomes of the 2019 gubernatorial elections in Bauchi state, Nigeria.
Keywords: Bauchi; Gubernatorial Elections; Infrastructural deterioration; Nigeria